Teaching Students with Disabilities: Hearing Impairments and Deafness - Blake C. Colclasure; Andrew C. Thoron; Sarah E. LaRose (EDIS)
This publication is one of the seven new articles that have been published in the Teaching Students with Disabilities series. This series provides useful information to ag-ed based instructors about different disabilities and how to teach those students in the unique environments posed by ag-ed, including classroom, laboratory, and non-formal environments. Written by Blake C. Colclasure, Andrew C. Thoron, and Sarah E. LaRose, and published by the Department of Agricultural Education and Communication, August 2016.